2014
DOI: 10.1073/pnas.1320265111
|View full text |Cite
|
Sign up to set email alerts
|

Loss of mTOR complex 1 induces developmental blockage in early T-lymphopoiesis and eradicates T-cell acute lymphoblastic leukemia cells

Abstract: mTOR is an evolutionarily conserved kinase that plays a critical role in sensing and responding to environmental determinants. Recent studies have shown that fine-tuning of the activity of mTOR complexes contributes to organogenesis and tumorigenesis. Although rapamycin, an allosteric mTOR inhibitor, is an effective immunosuppressant, the precise roles of mTOR complexes in early T-cell development remain unclear. Here we show that mTORC1 plays a critical role in the development of both early T-cell progenitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 36 publications
1
69
0
Order By: Relevance
“…S16B). In vivo, mTOR is a critical component of signal transduction-induced thymic T-cell maturation (23,24) and development of the embryonic heart (25). Consistent with these observations, we found increased phosphorylation of the mTOR targets S6, S6 kinase, and 4E-BP1 when comparing freshly isolated thymocytes to mature T cells or embryonic heart to adult heart ( Fig.…”
Section: Gw182 Expression Risc Assembly and Microrna Function Aresupporting
confidence: 86%
“…S16B). In vivo, mTOR is a critical component of signal transduction-induced thymic T-cell maturation (23,24) and development of the embryonic heart (25). Consistent with these observations, we found increased phosphorylation of the mTOR targets S6, S6 kinase, and 4E-BP1 when comparing freshly isolated thymocytes to mature T cells or embryonic heart to adult heart ( Fig.…”
Section: Gw182 Expression Risc Assembly and Microrna Function Aresupporting
confidence: 86%
“…The data indicate that mTOR signaling is important for HSC aging [43]. Rictor-NULL BM contributed to lower levels of the lymphoid lineages [44,45] cKO (Lck-Cre) T cells Deletion of Rictor impaired Notch-driven proliferation and differentiation of pre-T cells [49] Raptor cKO (Mx-Cre) BM Raptor KO BM cells cannot reconstitute the recipients [44] cKO (Lck-Cre) T cells Deletion of Raptor resulted in cell cycle abnormalities in early T cell progenitors [47] cKO (Vav-Cre) RBCs Raptor-deficient mice acquired anemia [57] RHEB cKO (CD4-Cre) T cells Rheb-deficient CD8 + T cells failed to differentiate into effector cells but retained memory characteristics [54] PTEN cKO (Mx-Cre) BM Pten-deficient adult HSCs gave only transient multi-lineage reconstitution that lasted less than 16 weeks after transplantation in all recipient mice [45] Sin1 KO T cells Sin1 deficiency results in an increased proportion of Foxp3(+) natural T-regulatory (nTreg) cells in the thymus [97] Deficiency in Raptor, an essential component of mTORC1, leads to the expansion of CD48 +…”
Section: Mtor In Hematopoiesismentioning
confidence: 99%
“…Evidence has shown that mTORC1 plays a more prominent role than mTORC2 in the development of early T cell progenitors. The deletion of Raptor, but not Rictor, resulted in cell cycle abnormalities in early T cell progenitors and generated defective T cell progenitors during the early T cell development in vivo and in vitro [47]. Under steady-state conditions, mTOR activity is kept low to allow normal T cell homeostasis.…”
Section: The Role Of Mtorc1 and Mtorc2 In T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, mTORC1 regulators Raptor and Rheb are dispensable for NKT17 differentiation (Wei et al, 2014). In contrast, loss of mTOR complex 1 (deletion of Raptor) induces developmental blockage in early T-lymphopoiesis and eradicates T-cell acute lymphoblastic leukemia cells, while deficiency of Rictor, an mTORC2 component, did not have the same effect (Hoshii et al, 2014). mTORC1 and mTORC2 differentially regulate homeostasis of neoplastic and nonneoplastic human mast cells (Smrz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%